Single-wavelength ring-cavity fiber laser with improved tunability based on nonlinear stimulated Brillouin scattering - Ahmad Hambali, Nor Azura Malini (2010)
Stimulated Brillouin scattering (SBS) is a nonlinear phenomenon that occurs in a optical fiber as a result of interaction between an injected coherent pump signal and an acoustic wave, resulting in backward propagating signal named Stokes wave. Practically for single-mode silica fiber (SMF), the Stokes wave was found to be downshifted by 0.08 nm (10 GHz) from the injected signal wavelength, through the Doppler effect. SBS generation has been considered generated a lot of interest for its deployment in a number of applications, such as microwave generation, frequency shifting, narrow-bandwidth amplification and fiber laser. This thesis focuses on the utilization of the nonlinear effects in dispersion compensating fiber (DCF),particularly the SBS to generate a single-wavelength laser in ring-cavity configurations. In this thesis, three types of fiber laser in ring-cavity configurations were investigated namely; Brillouin fiber laser (BFL), Brillouin Erbium fiber laser (BEFL), and Brillouin Raman fiber laser (BRFL). All the results presented in this thesis have been published. For ring cavity BFL, the lowest Brillouin threshold power of 0.9 mW, Brillouin signal (BS) peak power of 7.28 mW and the flatness of the BS power were obtained. The lasing wavelength of BFL structure can be tuned freely in the cavity because the laser structure does not produce any self-lasing cavity modes. The lasing wavelength is strictly dependent on the BP wavelength and subject to the availability of amplification bandwidth. The impact of Erbium-doped fiber amplifier (EDFA) location in the BEFL structure was investigated. A single-wavelength BEFL-1 structure in which the Brillouin pump (BP) is pre-amplified before entering the DCF produced 25.1 mW of BS signal power and tuning range of 50 nm. In contrast the BS signal power of 15.5 mW and 1.4 mW was obtained from BEFL-2 and BEFL-3, which can only be tuned over 28 nm and 3 nm respectively. In conclusion, the BEFL-1 generated higher gain efficiency to suppress the self-lasing-cavity modes in the cavity and provided higher BS signal power. Next, the characteristics of this BEFL structure in which the BP is pre-amplified before entering the DCF was demonstrated with variation of output coupling ratios from 10% to 99%. The highest BS signal power of 28.7 mW and wider tuning range over 60 nm without any self-lasing cavity modes were obtained. For the final experiment, the BRFL characteristics in terms of BS signal power,threshold power and tuning range were reported. The BS signal power of 2.71 mW,threshold power of 27 mW and BS signal power flatness of 26 nm were obtained. It is evidently shown that the BRFL can be operated freely without any appearance of the self-lasing cavity modes for all cases of the injected RPU power.